2021
DOI: 10.1002/vetr.25
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of cytological quality between fine‐needle aspiration and non‐aspiration techniques for obtaining ultrasound‐guided samples from canine and feline lymph nodes

Abstract: Background: In small animal medicine, ultrasound‐guided fine‐needle lymph node sampling plays a pivotal role in the diagnostic investigation of a range of pathologies including the staging of neoplastic disease. Traditionally fine needle aspiration cytology (FNAC) has been employed to produce samples, but fine needle non‐aspiration cytology (FNNAC) has been suggested to generate superior sample quality and diagnosticity. Methods: In a randomised control trial, 104 canine and feline lymph nodes were each sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In comparison, an aspiration technique has been reported superior in five different canine tumor 8 . Similar results between both techniques have been reported in multiple organs in humans 11,12 and conflicting results between aspiration and non‐aspiration technique have been found in canine lymph nodes 13,14 …”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In comparison, an aspiration technique has been reported superior in five different canine tumor 8 . Similar results between both techniques have been reported in multiple organs in humans 11,12 and conflicting results between aspiration and non‐aspiration technique have been found in canine lymph nodes 13,14 …”
Section: Introductionmentioning
confidence: 76%
“…8 Similar results between both techniques have been reported in multiple organs in humans 11,12 and conflicting results between aspiration and non-aspiration technique have been found in canine lymph nodes. 13,14 In our institution, there is a large discrepancy in the preferred needle gauge size between different board-certified radiologists and diagnostic imaging residents. Based on our review of the literature, there are no veterinary studies objectively investigating the effect of needle gauge in the diagnostic quality of ultrasound-guided FNA of the liver and spleen in dogs.…”
mentioning
confidence: 98%
“…6 While it has been shown that suction increases the number of cells collected in some tumors and organs, 31,32 there is no consensus on the best technique for FNA in veterinary or human medicine. 33,34 While some studies in the veterinary field seem to favor the fine-needle nonaspiration variant, 35 others recommend the use of suction 32 or have shown no differences among these variants. 34 As such, students probably should learn both techniques, and the model used herein allowed their practice.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys among veterinary practitioners have shown that 2/3 of clinicians routinely applied suction during sample harvesting 6 . While it has been shown that suction increases the number of cells collected in some tumors and organs, 31,32 there is no consensus on the best technique for FNA in veterinary or human medicine 33,34 . While some studies in the veterinary field seem to favor the fine‐needle nonaspiration variant, 35 others recommend the use of suction 32 or have shown no differences among these variants 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Aspiration of the liver is recommended for the detection of lymphoma regardless of its ultrasonographic appearance [ 18 ]. The fine-needle non-aspiration technique was found to be superior to the aspiration technique [ 19 , 20 ]. Ultrasound-guided fine-needle sampling of the liver requires at least two to three aspirates randomly collected from the liver to increase diagnostic accuracy, and it is routinely performed from the left lateral or left medial lobe liver [ 6 ].…”
Section: Introductionmentioning
confidence: 99%